2010
DOI: 10.1007/s12031-010-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of PACAP/VIP System in the Synaptic Transmission in the Hippocampus

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) are two closely related peptides, which can activate protein kinase A (PKA). At least three receptors for PACAP and VIP have been identified. The PACAP-specific receptor, PAC1 receptor, exhibits a higher affinity for PACAP than VIP, whereas VIP receptors, VPAC1-R and VPAC2-R, have similar affinities for PACAP and VIP. Both PACAP/VIP and their cognate receptors are highly expressed in the brain, including the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 58 publications
3
45
0
Order By: Relevance
“…Rodent studies of PACAP show that it has neurotrophic effects (24,26) and may facilitate synaptic plasticity (25,27). Plasticity in the amygdala and hippocampus is crucial to multiple forms of memory, playing a central role in reinforcement learning and declarative memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent studies of PACAP show that it has neurotrophic effects (24,26) and may facilitate synaptic plasticity (25,27). Plasticity in the amygdala and hippocampus is crucial to multiple forms of memory, playing a central role in reinforcement learning and declarative memory.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the hippocampus, another brain region that plays a central role in PTSD (22), where PACAP binding sites are particularly dense (23) and where PACAP has been shown to act in a neuroprotective or neurotrophic manner (24)(25)(26) and may facilitate synaptic plasticity (25,27). We predicted that individuals with the risk polymorphism would show exaggerated amygdala responses to threat stimuli and decreased functional connectivity between the amygdala and the hippocampus and medial prefrontal cortex, regions that regulate amygdala reactivity (28,29).…”
Section: Significancementioning
confidence: 99%
“…PACAP38 has been also shown to induce a form of long-term depression (LTD) in hippocampal neurons that requires interaction of AMPA receptor subunits with scaffolding proteins (Kondo et al 1997;Roberto et al 2001;Ster et al, 2009), thus validating its role in learning and memory. This has been further confirmed by the use of transgenic animals (Yang et al, 2010). Nonetheless, the mechanism by which PACAP38-dependent signaling can modify AMPA receptors remains almost unknown and no information is available on the effect of PACAP38 on AMPA receptor subunit localization at the synapse.…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that PACAP38 modulates a variety of signaling pathways within the excitatory glutamatergic synapse (MacDonald et al, 2005;Yang et al, 2009;Yang et al, 2010), ranging from activation of different protein kinases, i.e. protein kinase A (PKA) and the mitogen-activated protein (MAP) kinase to the mobilization of calcium (Harmar et al, 1998;Vaudry et al, 2000;Kojro et al, 2006;Ohnishi et al, 2008;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pentylenetetrazol-induced seizures resulted in short term decrease in the level of VIP [57,201]. VIP has an overall excitatory action on synaptic transmission in the hippocampus [202], in which the cAMP-mediated activation of NMDA receptor plays a role [203]. Still, VIP was neuroprotective in some models of neurodegeneration including neuroinflammation [204] and beta-amyloidinduced neurodegeneration [205] providing the possible neuroprotective role in epileptic sclerosis.…”
Section: Vasoactive Intestinal Peptidementioning
confidence: 99%